The Evolution of Soundscape Appraisal Through Enactive Cognition - van den Bosch, Kirsten A.-M.; Welch, David; Andringa, Tjeerd C. (Frontiers in Psychology, 2018)
We propose a framework based on evolutionary principles and the theory of enactive cognition (“being by doing”), that addresses the foundation of key results and central questions of soundscape research. We hypothesize that the two main descriptors (measures of how people perceive the acoustic environment) of soundscape appraisal (‘pleasantness’ and ‘eventfulness’), reflect evolutionarily-old motivational and affective systems that promote survival through preferences for certain environments and avoidance of others. Survival is aimed at ending or avoiding existential threats and protecting viability in a deficient environment. On the other hand, flourishing occurs whenever survival is not an immediate concern and aims to improve the agent’s viability and by co-creating ever better conditions for existence. As such, survival is experienced as unpleasant, and deals with immediate problems to be ended or avoided, while flourishing is enjoyable, and therefore to be aimed for and maintained. The absence of threats to survival and flourishing are perceived as pleasant states, whereas threats to survival or a lack of opportunities to remain viable are unpleasant. Therefore, the simplest, safety-relevant meaning attributable to soundscapes (audible safety) should be key to understanding soundscape appraisal. To strengthen this, we show that the auditory nervous system is intimately connected to the parts of our brains associated with arousal and emotions. Furthermore, our theory demonstrates that ‘complexity’ and ‘affordance content’ of the perceived environment are important underlying soundscape indicators (measures used to predict the value of a soundscape descriptor). Consideration of these indicators allows the same soundscape to be viewed from a second perspective; one driven more by meaning attribution characteristics than merely emotional appraisal. The synthesis of both perspectives of the same person-environment interaction thus consolidates the affective, informational, and even the activity related perspectives on soundscape appraisal. Furthermore, we hypothesize that our current habitats are not well matched to our, evolutionarily old, auditory warning systems, and that we consequently have difficulty establishing audible safety. This leads to more negative and aroused moods and emotions, with stress-related symptoms as a result.